The Formation Of Students' Religious Character Through Scouting Extracurricular Activities At Al Farabi Junior High School - Anggriani, Dinda; Agustia, Nanda Rahayu (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This study aims to analyze the formation of students' religious character through Scout extracurricular activities at SMP Al Farabi. The formation of a religious character is a crucial aspect of education that seeks to create a generation that is not only intellectually intelligent but also possesses strong spiritual values. This research is a descriptive qualitative study using pedagogical and sociological approaches. The data sources in this study include male and female Scout coaches, Scout administrators at SMP Al Farabi, the head of the school, and students. Data collection techniques employed are observation, interviews, and documentation. Subsequently, data processing and analysis were carried out in three stages: data reduction, data presentation, and verification or conclusion drawing. The validity of the data in this study was ensured through triangulation. The results show that Scout activities at SMP Al Farabi are designed to integrate religious values, such as honesty, responsibility, discipline, and compassion for others. These values are instilled through various activities such as group prayers, internalization of Pancasila values, and lessons in teamwork. Scout activities have proven effective in supporting the development of students' religious character, as evidenced by positive changes in their behavior and attitudes both in the school environment and in society. This study recommends optimizing extracurricular activities based on religious values to holistically support the goals of character education.